The Formation of Ethiopia’s Federation and its Implications for the Amharas’ Quest for Recognition and Boundary Demarcations - Ketemaw Muluye (Modern Africa)
Federations are structural arrangements with the tenets of shared rule and self-rule. These federations may be formed through coming-together, holding-together, or putting-together processes. This article aims to situate Ethiopia in one of these three variants and examine its implications for the Amharas’ quest for boundary demarcations and equal recognition in other regions. The data were collected through interviews and document analysis. Accordingly, the article argues that Ethiopia is a putting-together federation because of major flaws committed during the transition. The putting-together federation left ethnic groups such as the Amhara without protection by regional constitutions. It also led to the sanctioning of boundary demarcations that contradicts the criteria listed under the federal constitution. Hence, it is recommended to restructure the federation through democratic bargaining.